An updated pharmacological insight into calotropin as a potential therapeutic agent in cancer - Rajkovic, Jovana; Novakovic, Radmila; Grujic-Milanovic, Jelica; Ydyrys, Alibek; Ablaikhanova, Nurzhanat; Calina, Daniela; Sharifi-Rad, Javad; Al-Omari, Basem (Frontiers in Pharmacology, 2023)
Calotropin is a pharmacologically active compound isolated from milkweed plants like Calotropis procera, Calotropis gigantea, and Asclepias currasavica that belong to the Asclepiadaceae family. All of these plants are recognised as medical traditional plants used in Asian countries. Calotropin is identified as a highly potent cardenolide that has a similar chemical structure to cardiac glycosides (such as digoxin and digitoxin). During the last few years, cytotoxic and antitumor effects of cardenolides glycosides have been reported more frequently. Among cardenolides, calotropin is identified as the most promising agent. In this updated and comprehensive review, we aimed to analyze and discuss the specific mechanisms and molecular targets of calotropin in cancer treatment to open new perspectives for the adjuvant treatment of different types of cancer. The effects of calotropin on cancer have been extensively studied in preclinical pharmacological studies in vitro using cancer cell lines and in vivo in experimental animal models that have targeted antitumor mechanisms and anticancer signaling pathways. The analyzed information from the specialized literature was obtained from scientific databases until December 2022, mainly from PubMed/MedLine, Google Scholar, Scopus, Web of Science, and Science Direct databases using specific MeSH search terms. The results of our analysis demonstrate that calotropin can be a potential chemotherapeutic/chemopreventive adjunctive agent in cancer pharmacotherapeutic management.